2021
DOI: 10.5603/psych.a2021.0043
|View full text |Cite
|
Sign up to set email alerts
|

Analiza stanu psychicznego i satysfakcji z pracy personelu medycznego w okresie pandemii COVID – 19

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
4
1
Order By: Relevance
“…In a group of the general population in Iran, 51% showed anxiety during the COVID-19 pandemic [ 51 ]. Contrary to our results, the study by Fukowska and Koweszko [ 52 ], which covered 316 healthcare workers and 302 control subjects who did not work in the health professions, found that healthcare professionals had higher levels of depression and anxiety than the control group, and nurses had the highest scores.…”
Section: Discussioncontrasting
confidence: 99%
“…In a group of the general population in Iran, 51% showed anxiety during the COVID-19 pandemic [ 51 ]. Contrary to our results, the study by Fukowska and Koweszko [ 52 ], which covered 316 healthcare workers and 302 control subjects who did not work in the health professions, found that healthcare professionals had higher levels of depression and anxiety than the control group, and nurses had the highest scores.…”
Section: Discussioncontrasting
confidence: 99%
“…All these factors mean that, on the one hand, conducting research on this issue will be of great importance for science [17,18,19], and on the other hand, it is difficult to predict how much will be able to run them.…”
Section: Analysis Of the Test Resultsmentioning
confidence: 99%
“…Numerous Polish studies have con rmed that the nursing staff is not satis ed with their professional role [30,31,32]. -11).…”
Section: Discussionmentioning
confidence: 99%